Aging-Related Moderation of the Link Between Compliance With International Physical Activity Recommendations and the Hemodynamic, Structural, and Functional Arterial Status of 3,619 Subjects Aged 3–90 Years - Zócalo, Yanina; Gómez-García, Mariana; Torrado, Juan; Bia, Daniel (Frontiers in Sports and Active Living, 2022)
Background Compliance with physical activity recommendations (CPARs) is associated with better health indicators. However, there are only few studies to date that have comprehensively analyzed the association between CPARs and cardiovascular status “as a whole” (e.g., analyzing hemodynamic, structural, and functional properties, and different arterial territories). The relationship between CPARs and cardiovascular properties could be strongly influenced by the growth and aging process. Aim The goal of the study is to investigate the association between CPAR and cardiovascular properties by placing special emphasis on: (i) identifying if there is an independent association, (ii) if the association is “moderated” by age, and (iii) to what extent the association depends on the arterial parameter (hemodynamic vs. structural vs. functional) and/or the arterial segment (e.g., central vs. peripheral; elastic vs. transitional vs. muscular arteries). Methods A total of 3,619 subjects (3–90 years of age) were studied. Extensive cardiovascular evaluations were performed. Cardiovascular risk factors (CRFs) and physical activity (PA) levels were determined. The subjects were categorized as compliant (n = 1, 969) or non-compliant (n = 1,650) with World Health Organization-related PA recommendations. Correlation and multiple regression models (including CPAR*Age interaction) were obtained, and Johnson-Neyman technique was used to produce regions of significance. Results The independent association between CPARs and cardiovascular characteristics were strongly moderated by age. The moderation was observed on a wide range of age but particularly notorious on the extremes of life. Certain arterial characteristics demonstrated opposite effects in relation to CPAR status depending on the range of age considered. The association between CPAR and cardiovascular characteristics was independent of CRFs and moderated by age. In subjects younger than 45–55 years, CPAR status was associated with lower central and peripheral blood pressure (i.e., the younger the subject, the higher the reduction). During adult life, as age increases in the subjects, CPARs was associated with a beneficial hemodynamic profile, which is not related with variations in pressure but strongly related with lower levels of waveform-derived indexes and ventricular afterload determinants. Conclusions The independent associations between CPARs and arterial properties were strongly moderated by age. Data provided by blood pressure levels and waveform-derived indexes would be enough to evaluate the independent association between CPARs and the vascular system in the general population.